Photo-catalyzed and phyto-mediated rapid green synthesis of silver nanoparticles using herbal extract of Salvinia molesta and its antimicrobial efficacy - Verma D.K.; Hasan S.H.; Banik R.M. (My University, 2025)
Current study presents an economic, ecofriendly and simple photo-catalytic green route for the swift biosynthesis of silver nanoparticles (AgNPs) within 20 s, devoid of any instrumental support or chemical reductant. Aqueous leaf-extract of an aquatic fern, Salvinia molesta (AES), was used as a bioreductant as well as a stabilizing agent. Rapid change in color of reaction mixture from yellowish green to reddish brown within 20 s in direct sun light exposure was considered as the primary visual indication of AgNPs biosynthesis. The biosynthesis of AgNPs was confirmed by UV-visible spectroscopy through the presence of a characteristic surface plasmon resonance (SPR) band for AgNPs at λmax of 425 nm. The process parameters were optimized through one factor at a time approach. Optimal values of different process parameters for the current biosynthetic system were found as; 35 min of reaction time under sun light, 8.0 mM AgNO3 concentration and 5.0% (v/v) AES inoculum dose. Field emission scanning electron microscopy (FESEM), energy dispersive X-Ray spectroscopy (EDX), high resolution transmission electron microscopy (HRTEM), atomic force microscopy (AFM) and X-ray diffraction (XRD) analysis showed that most of AgNPs were spherical in shape with average size distribution of 12.46 nm having face centered cubic (fcc) crystal lattice. IR analysis of AES and synthesized AgNPs indicated the involvement of both hydroxyl and amino groups in the biosynthesis and stabilization of AgNPs. The synthesized AgNPs were found to be an effective antibacterial agent against both Gram positive and Gram negative bacteria. On the basis of results and facts, a probable mechanism has also been proposed to explore the possible route of biosynthesis of AgNPs through AES. © 2015 Elsevier B.V. All rights reserved.